Scientific societies have a part to play in repatriating fossils - de Araújo-Júnior, Hermínio Ismael; Ghilardi, Renato Pirani [UNESP]; Ribeiro, Victor Rodrigues [UNESP]; Ribeiro, Ana Maria; Barbosa, Fernando Henrique de Souza; Negri, Francisco Ricardo; Scheffler, Sandro Marcelo (Springer Nature, 2024)
The Brazilian Society of Palaeontology (BSP) has recently taken steps to become more involved in the repatriation of fossil specimens — a central issue in the global palaeontological community, as interest in combating scientific colonialism grows — both through collaboration with researchers and other Latin American scientific associations. We discuss our experience, including the challenges we have faced and how we have overcome them, in the hope of inspiring other scientific societies to play their part.